Low Dose Effects in Psychopharmacology: Ontogenetic Considerations - Linda Patia Spear; Elena I. Varlinskaya (SAGE Publishing, 2005)
Low doses of psychoactive drugs often elicit a behavioral profile opposite to that observed following administration of more substantial doses. Our laboratory has observed that these effects are often age-specific in rats. For instance, whereas moderate to high doses of the dopamine agonist apomorphine increase locomotion, suppressed locomotor activity is seen following low dose exposure, with this low dose effect not emerging consistently until adolescence. A somewhat earlier emergence of a low dose "paradoxical" effect is seen with the 5HT 1a receptor agonist, 8-OH-DPAT, with late preweanling, but not neonatal, rats showing increases in ingestive behavior at low doses but suppression at higher doses. In contrast to these ontogenetic increases in expression of low dose drug effects, low dose facilitation of social behavior is seen following ethanol only in adolescent rats and not their mature counterparts, although suppression of social interactions at higher doses is seen at both ages. This hormesis-like low dose stimulation appears related in part to overcompensation, with brief social suppression preceding the subsequent stimulation response, and also bears a number of ontogenetic similarities to acute tolerance, a well characterized, rapidly emerging adaptation to ethanol. Implications of these and other ontogenetic findings for studies of hormesis are discussed.